Enhanced recovery after cesarean protocol versus traditional protocol in elective cesarean section: A prospective observational study - Sunanda Gupta; Apoorva Gupta; Aditi S Baghel; Karuna Sharma; Savita Choudhary; Vidhu Choudhary (Wolters Kluwer Medknow Publications, 2022)
Background: Enhanced recovery programs result in reduced morbidity in terms of effective pain control, reduced length of stay (LOS), and an earlier return to normal activities. This study has been conducted to compare Enhanced recovery after caesarean (ERAC) protocol to traditional care of cesarean section (CS) in our institute. Materials and Methods: Patients undergoing elective CS were subjected to ERAC protocol (Group A; n = 100) for first six months and traditional protocol (Group B; n = 100) for next six months. Primary outcome was comparison of total duration of stay (readiness to discharge) in the hospital, whereas secondary objectives were intraoperative hemodynamic control and requirement of vasopressor, comparison of Visual Analogue Scale (VAS) scores and requirement of analgesics in 24 hrs, barriers to implementation of ERAC components, urinary retention and need of recatheterization and any adverse events perioperatively. Results: Significant reduction in LOS or readiness for discharge was found in Group A; 2.85 ± 0.5 vs 5.25 ± 0.61 hrs in Group B (p < 0.0001). Episodes of hypotension and requirement of phenylephrine was significantly more in Group B. (p < 0.0001) VAS scores in Group A were significantly less postoperatively with significant reduction in consumption of rescue analgesic in 24 hrs. (p < 0.001) Components of ERAC protocol were implemented successfully with significant difference in time of ambulation, decatheterization, and resumption of oral feed postoperatively. Conclusion: Implementation of ERAC results in significant reduction in LOS in hospital with better pain relief and reduced postoperative opioid requirement following cesarean delivery.